2015
DOI: 10.1080/15548627.2015.1061846
|View full text |Cite
|
Sign up to set email alerts
|

Export-deficient monoubiquitinated PEX5 triggers peroxisome removal in SV40 large T antigen-transformed mouse embryonic fibroblasts

Abstract: Peroxisomes are ubiquitous cell organelles essential for human health. To maintain a healthy cellular environment, dysfunctional and superfluous peroxisomes need to be selectively removed. Although emerging evidence suggests that peroxisomes are mainly degraded by pexophagy, little is known about the triggers and molecular mechanisms underlying this process in mammalian cells. In this study, we show that PEX5 proteins fused to a bulky C-terminal tag trigger peroxisome degradation in SV40 large T antigen-transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
94
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 88 publications
3
94
0
Order By: Relevance
“…PEX5 is ubiquitinated in yeast and mammals as it is recycled back into the cytosol for further import rounds [9], making ubiquitinated PEX5 an attractive candidate pexophagy signal. Indeed, preventing efficient retrotranslocation of PEX5 by addition of a bulky C-terminal tag can trigger peroxisome degradation via autophagy in a mammalian cell line [79]. In addition, knockdown of the docking protein PEX14 reduces pexophagy in mammals [73], which might indicate that mammalian PEX14 is directly required to bind a pexophagy receptor or that PEX14 is indirectly required because it is needed to import the actual pexophagy signal, be it ubiquitinated PEX5, a PEX5-dependent matrix protein, or a PEX5-dependent process (e.g., oxidative damage).…”
Section: How Do Plant Peroxisomes Signal For Their Destruction?mentioning
confidence: 99%
“…PEX5 is ubiquitinated in yeast and mammals as it is recycled back into the cytosol for further import rounds [9], making ubiquitinated PEX5 an attractive candidate pexophagy signal. Indeed, preventing efficient retrotranslocation of PEX5 by addition of a bulky C-terminal tag can trigger peroxisome degradation via autophagy in a mammalian cell line [79]. In addition, knockdown of the docking protein PEX14 reduces pexophagy in mammals [73], which might indicate that mammalian PEX14 is directly required to bind a pexophagy receptor or that PEX14 is indirectly required because it is needed to import the actual pexophagy signal, be it ubiquitinated PEX5, a PEX5-dependent matrix protein, or a PEX5-dependent process (e.g., oxidative damage).…”
Section: How Do Plant Peroxisomes Signal For Their Destruction?mentioning
confidence: 99%
“…Thus the identification of a physiological link between mammalian ubiquitination and pexophagy would constitute a significant advance in the field. Two related studies, by Zhang et al 6 (published in this issue) and Nordgren et al 7 now identify PEX5 as the physiological ubiquitination target that promotes pexophagy.…”
mentioning
confidence: 90%
“…This naturally raises the question as to why ubiquitination at these residues in PEX5 does not also target it for pexophagy. Indeed this can happen, as shown by the demonstration that the N-terminal mono-ubiquitination of PEX5 at Cys11 induces pexophagy in SV40 T antigen-transformed mouse embryonic fibroblasts 7 . These authors found that PEX5 fused to a bulky C-terminal tag was delivered to peroxisomes and mono-ubiquitinated at Cys11, but its failure to be exported from peroxisomes triggered pexophagy (Fig.…”
mentioning
confidence: 98%
See 2 more Smart Citations